Philopatry and dispersal of juvenile leervis Lichia amia (Teleostei: Carangidae) tagged in a warm-temperate South African estuary. Issue 1 (2nd January 2017) - Murray, T; Cowley, P; Childs, A-R; Bennett, R
Abstract : Understanding and characterising movement and area-use patterns of fishes within estuaries, as well as understanding the degree of connectivity between estuaries and the marine environment, can provide important insights into a species' ecology, which is fundamental for effective management and conservation. Mark-and-recapture data obtained from the 082 TAG FISH Project, a dart-tagging programme, were used to describe movement patterns of juvenile leervis Lichia amia in the permanently open Swartkops Estuary, South Africa, as well as the degree of connectivity with the adjacent marine environment. A total of 628 juvenile leervis were tagged from 2008 to 2015, of which 77 fish (12.3%) were recaptured, with juveniles comprising 85.7% of all measured recaptures. The majority of recaptures (75.3%) were made within the Swartkops Estuary, indicating estuarine philopatry, with 23.4% having moved less than 1 km, revealing site fidelity, but most (51.9%) displaying estuarine roaming. A smaller portion of recaptures (27.7%) had dispersed to other habitats; 16 (20.8%) displayed multiple-habitat connectivity, while only 3 (3.9%) had undertaken long-distance movements (>100 km) and were recaptured up to 825 km northeast of the Swartkops Estuary. Lichia amia that had moved greater distances were characterised by a greater mean size and age at the time of recapture. This study provides valuable information on the philopatry and dispersal of juvenile L. amia .